Energy harvesting from wind-induced bridge vibrations via electromagnetic transduction. (15th May 2016) - Caruso, Giovanni; Chirianni, Gianluca; Vairo, Giuseppe
Highlights: Energy-harvesting feasibility from wind-excited bridges via electromagnetic devices is shown. Dynamical coupling among adaptative tuned-mass harvesters and bridge is accounted for. An optimisation approach to maximise extracted power from aeroelastic vibrations is proposed. Wind velocity and wind incidence angle greatly affect the harvested power. A simplified uncoupled model and a simplified tuning procedure are successfully proposed. Abstract: Energy harvesting from wind-induced vibrations of long-span bridges through electromagnetic devices is herein addressed. A coupled model, describing the bridge structure excited by aeroelastic wind forces and equipped with harvesting devices mounted along the bridge girder, is derived by reducing bridge dynamics via a modal analysis. The model is employed to maximise the harvested power with respect to the stiffness and the electromagnetic damping parameter of the harvesting devices, depending on the characteristics of the approaching wind flow. Numerical results obtained in the case of a bridge-like structure similar to the Great Belt East Bridge are presented and discussed, showing model soundness and effectiveness. The influence of the dynamical coupling among principal structure and harvesting devices on the harvesting process is investigated. Moreover, in order to overcome possible feasibility drawbacks related to a real-time adjustment of harvester parameters, a simplified tuning procedure is proposed, resulting effective in a wide wind-speed range.